Comparative literature for non-philology majors: the general education experience at New Bulgarian University (Colloquia Comparativa Litterarum, 2025)
The paper presents the author’s personal experience as a lecturer within the system of general education at New Bulgarian University. It discusses the problems of teaching literature to students who do not major in linguistic specialties. One of the conclusions of the text is that the overcoming of these problems is impossible without the involvement of comparative literature studies.
Keywords: teaching literature to students who do not major in linguistic specialties; comparative literature studies